Penny pricing and the components of spread and depth changes - Chung, Kee H.; Charoenwong, Charlie; Ding, David K. (Journal of Banking & Finance, 2004)
Recent studies show that decimal pricing led to significant reductions in the spread and depth on the NYSE. In this paper, we examine how the observed changes in the spread and depth can be attributed to different factors. We show that stocks with higher proportions of one-tick spreads and odd-sixteenth quotes, and more frequent trading before decimalization experienced larger declines in the spread and depth afterwards. We interpret this result as evidence of reduced binding constraints and increased price competition under decimal pricing. We also find that decimal pricing led to nontrivial changes in select stock attributes, and that these changes exerted an additional impact on spreads and depths. Our results suggest that sub-penny pricing may further reduce the spreads of high-volume, low-risk, or low-price stocks.